2000
DOI: 10.1515/jpm.2000.057
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal echocardiograms of macrosomic neonates

Abstract: IVS/PW ratio of macrosomic infants fell outside of the normal range. Macrosomic neonates were found to have an increased SF% secondary to a proportionally smaller LVES volume, regardless of IVS thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…This is in agreement with [11] who observed that cardiac diameters were more in macrosomic than control ,also more in macrosomic of IDM than those of non IDM. To the contrary to our results, a study was done by [12] on 9 healthy full term AGA neonates and 15 macrosomic neonates; Echocardiography was done, and showed a similar cardiac measurement in macrosomic neonates and control except mean LVES volume was smaller in macrosomic neonates than in control which resulted in increased FS (fractional shortening),and this could be attributed to a small sample size in their study.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with [11] who observed that cardiac diameters were more in macrosomic than control ,also more in macrosomic of IDM than those of non IDM. To the contrary to our results, a study was done by [12] on 9 healthy full term AGA neonates and 15 macrosomic neonates; Echocardiography was done, and showed a similar cardiac measurement in macrosomic neonates and control except mean LVES volume was smaller in macrosomic neonates than in control which resulted in increased FS (fractional shortening),and this could be attributed to a small sample size in their study.…”
Section: Discussioncontrasting
confidence: 94%
“…In the current study: in macrosomic neonates males were (28) represent of cases 70% of cases while females were (12) represented 30%; All neonates in our study were full term with range from 37 to 40 week of gestational age, Our results are in accordance with results of [7] .…”
Section: Discussionsupporting
confidence: 91%
“…Large-forgestational age (LGA) fetuses have an increased risk of interventricular septal hypertrophy, cardiomyopathy, cardiac arrhythmias, and biomarkers of myocardial ischemia as compared with those that are appropriate-for-gestational age (AGA). [8][9][10][11] These alterations in cardiac function among LGA infants have been reported both in utero and postnatally, even in the absence of maternal diabetes. [9][10][11][12][13][14][15] Electrocardiographic ST-segment analysis provides a measure of myocardial ischemia.…”
mentioning
confidence: 87%
“…[8][9][10][11] These alterations in cardiac function among LGA infants have been reported both in utero and postnatally, even in the absence of maternal diabetes. [9][10][11][12][13][14][15] Electrocardiographic ST-segment analysis provides a measure of myocardial ischemia. [16][17][18] In the setting of fetal cardiac hypoxia, ST-depression and ST-elevation can occur as a result of abnormal repolarization of the myocardium.…”
mentioning
confidence: 87%
See 1 more Smart Citation